Metallica : back to the front; a fully authorized visual history of the master of puppets album and tour - Taylor, Matt; Metallica (Musical group). (San Rafael, CA : Insight Editions, 2016)
"For the first time, Metallica: Back to the Front tells the fully authorized story of the creation of the Master of Puppets album and the subsequent tour. Featuring new and exclusive interviews with band members James Hetfield, Lars Ulrich, and Kirk Hammett, this is the definitive account of the most venerated period of Metallica$1 (Bs history, from the incredible highs of touring in support of Ozzy Osbourne to the lows of losing a key member of the band and crucial part of the Metallica sound. Metallica: Back to the Front will also feature interviews with other important figures in the band$1 (Bs history, including managers Cliff Burnstein and Peter Mensch, Faith No More guitarist Jim Martin, Anthrax band members Scott Ian and Charlie Benante, and many, many more"--Amazon.s
Keywords: Metallica (Musical group); Metallica (Musical group); Heavy metal (Music); Heavy metal (Music)